MATA UANG LOGAM CINA: SALAH SATU SARANA REKONSTRUKSI SEJARAH - Yuniarso K. Adi (BRIN, 1994)
Currency is one of the decisive means of trade and economic activity. This has happened since people began to recognize trade and price. The first societies to recognize and use currency as an official medium of exchange and value standards were Egypt, Greece and China. Chinese trading activities began to penetrate Southeast Asia since the second century BC. One of the artifactual evidence that can help reveal China's trading activities in Indonesia is Chinese coins. The study of Chinese coin inscriptions is an effort to contribute to the provision of new analytical data for the interpretation of historical data in the hope that it can be used to help reconstruct history. This needs to be done because until now, the written data that has been presented and obtained by experts to interpret the activities of trade relations between China and Indonesia in the early days have been based more on Chinese news.